Overlap of Pink-footed Shearwaters and central Chilean purse-seine fisheries: Implications for bycatch risk. (19th June 2019) - Carle, Ryan D; Felis, Jonathan J; Vega, Rodrigo; Beck, Jessie; Adams, Josh; López, Verónica; Hodum, Peter J; González, Andrés; Colodro, Valentina; Varela, Tiare
Abstract: Understanding susceptibility of seabirds to fisheries bycatch requires quantifying overlap of seabird at-sea habitat with fisheries' distribution and effort. Pink-footed Shearwaters ( Ardenna creatopus ) are vulnerable seabirds that breed only in Chile. Recently, high rates of Pink-footed Shearwater bycatch (i.e. >1, 500 observed mortalities 2015–2017) were documented by observers in central Chilean purse-seine fisheries. We present analysis of Pink-footed Shearwater at-sea movements and overlap with central Chilean purse-seine fleets targeting common sardine ( Strangomera bentincki ), Peruvian anchoveta ( Engraulis ringens ), and Chilean jack mackerel ( Trachurus murphyi ). To determine overlap during 2015–2017, we paired locations from 49 Pink-footed Shearwaters rearing nestlings at Isla Mocha, Chile, with locations and number of observed purse-seine sets in central Chile. Pink-footed Shearwaters typically visited waters ≤30 km offshore throughout central Chile. Foraging trip durations varied interannually, with longer trips in 2016, but all years revealed persistent foraging hotspots near Valdivia, the Gulf of Arauco, and Isla Mocha, Chile. Greatest overlap between Pink-footed Shearwaters and fisheries occurred with the sardine/anchoveta fleet near Valdivia (artisanal and industrial) and the Gulf of Arauco (artisanal); overlap with the jack mackerel fleet was minimal. Given Pink-footed Shearwater bycatch documented in these fisheries, this overlap may indicate risk of bycatch for these birds, although we did not directly quantify shearwater–fisheries interaction. Our results can inform further fishery monitoring efforts, as well as collaboration among scientists, managers, and fishers to identify, quantify, and reduce fisheries bycatch of Pink-footed Shearwaters within Chile and internationally.